2021
DOI: 10.3390/ijms222212167
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Microenvironment-Mediated Chemoprotection through Stromal Galectin-3 Inhibition in Acute Lymphoblastic Leukemia

Abstract: Environmentally-mediated drug resistance in B-cell precursor acute lymphoblastic leukemia (BCP-ALL) significantly contributes to relapse. Stromal cells in the bone marrow environment protect leukemia cells by secretion of chemokines as cues for BCP-ALL migration towards, and adhesion to, stroma. Stromal cells and BCP-ALL cells communicate through stromal galectin-3. Here, we investigated the significance of stromal galectin-3 to BCP-ALL cells. We used CRISPR/Cas9 genome editing to ablate galectin-3 in stromal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…The reduced sensitivity to chemotherapeutic drugs and oxidative stress of leukemic cells co-cultured with stromal cells has been reported previously [ 11 , 12 , 13 , 14 , 15 , 33 , 34 , 35 ]. Co-cultures of mouse and human cells have been used to study this effect [ 11 , 14 , 34 , 35 ], and the intercellular transfer of mitochondria, vesicles, and galectin-3 from MSC to leukemic cells, has been associated with this protection in experimental settings where transfer goes from human to human [ 9 , 15 , 16 , 36 ] and from mouse to human cells [ 11 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The reduced sensitivity to chemotherapeutic drugs and oxidative stress of leukemic cells co-cultured with stromal cells has been reported previously [ 11 , 12 , 13 , 14 , 15 , 33 , 34 , 35 ]. Co-cultures of mouse and human cells have been used to study this effect [ 11 , 14 , 34 , 35 ], and the intercellular transfer of mitochondria, vesicles, and galectin-3 from MSC to leukemic cells, has been associated with this protection in experimental settings where transfer goes from human to human [ 9 , 15 , 16 , 36 ] and from mouse to human cells [ 11 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 54%
“…The reduced sensitivity to chemotherapeutic drugs and oxidative stress of leukemic cells co-cultured with stromal cells has been reported previously [ 11 , 12 , 13 , 14 , 15 , 33 , 34 , 35 ]. Co-cultures of mouse and human cells have been used to study this effect [ 11 , 14 , 34 , 35 ], and the intercellular transfer of mitochondria, vesicles, and galectin-3 from MSC to leukemic cells, has been associated with this protection in experimental settings where transfer goes from human to human [ 9 , 15 , 16 , 36 ] and from mouse to human cells [ 11 , 14 , 15 , 16 ]. In these reports, cells interacted in 2D co-cultures, in which leukemic cells grew on top of a monolayer of stromal cells; only the work of Kolba and coworkers, using the Trans-SILAC method and chronic myeloid leukemia cells, provided a proteome-scale map of the transferred proteins [ 9 ].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…While less is known about the BMM of B-ALL, studies have shown that MSCs promote engraftment, survival and chemoresistance of B-ALL cells (Iwamoto et al, 2007;Nwabo Kamdje et al, 2011;Frolova et al, 2012;Jacamo et al, 2014;Hu et al, 2015;Mallampati et al, 2015;Polak et al, 2015;Burt et al, 2019;Portale et al, 2019;Yu et al, 2019;Ruiz-Aparicio et al, 2020;Tarighat et al, 2021). Furthermore, B-ALL cells are capable of disrupting the proliferation, differentiation, protein expression, signaling pathway activation and hematopoietic-supporting capabilities of MSCs (Conforti et al, 2013;Jacamo et al, 2014;van den Berk et al, 2014;Vicente Lopez et al, 2014;Polak et al, 2015;Balandran et al, 2016;de Rooij et al, 2017;Vernot et al, 2017;Ma et al, 2019;Portale et al, 2019;Yu et al, 2019;Verma et al, 2020;Vanegas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%